Discovering Pre-Service English Teachers' Orientations and Experiences in Designing Communicative Language Teaching Based-Activities by Using Islamic Songs - Megawati, Fika; Agustina, Sheila; Wulandari, Fitria; Salsabila, Saffana; Salsabila, Nada; Sinta, Nanda Aprila (JOLLT Journal of Languages and Language Teaching, 2024)
Developing learning tools is a skill that a teacher needs to master. In this case, learning English requires material appropriate to real-life, called Communicative Language Teaching (CLT) so that the language mastered by students is the language that is applied in everyday life, including the use of songs. Although many studies have explored songs for English language learning, the integration of Islamic songs in English classroom activities has not been widely discussed. Therefore, this research aims to investigate the viewsand practice of prospective English teachers on the integration of Islamic songs. The method used is a qualitative approach involving analyzing online interviews and teaching module documents prepared by prospective teachers. The results show that the consideration for selecting songs expressed by the prospective teacher is based on three orientations, namely pedagogical, psychological, and cultural. Regarding the worksheet design, participants prefer giving fill-in-the-blank format as the main assessment in measuring students' level of understanding. This research implies that CLT is good for EFL class, so the pedagogical knowledge possessed by prospective teachers need to be fostered, particularly in selecting the appropriate content of the song and adjusting it to create various communicative and meaningful activities for EFL learners.